Analisis Investasi Kebutuhan Alat Muat (excavator) dan Alat Angkut (dumptruck) pada Penambangan Batu Kapur untuk Memenuhi Target Produksi 900.000 ton/bulan di Quarry PT. Semen Padang - Fachri Arif; Yoszi Mingsi Anaperta (Departemen Teknik Pertambangan FT UNP, 2021)
Abstract. The process of loading and transporting limestone at PT. Semen Padang from the mining front towards crusher using a combination of mining equipment Excavator Caterpillar 6030 BH and Dump Truck Komatshu 785. Based on company data, target productions of limestone estimate 900.000 ton/month. In reality in fact of first three month of 2018 were 2.2 million ton, in January were 768.321 ton, February were 748.252 ton, and in March were 759.636 ton. This study chosees whether to buy or rent an equipment that is more effectively used in limestone mining by using ecomomic analysis Present Worth Cost (PWC) and Future Worth Cost (FWC) in terms of the smallest costs used. Differences in costs incurred between the cost of buying and renting equipment after doing calculations with analysis Present Worth Cost (PWC) and Future Worth Cost (FWC) for one loading unit Excavator Cat 6030, PWC= Rp. 47.931.918.250 and FWC= Rp. 57.172.394.270, while for two units of transportation Komatsu HD 785, PWC= Rp. 16.785.906.482 and FWC= Rp. 1.157.760.340. The results of calculations using analysis Present Worth Cost (PWC) and Future Worth Cost (FWC) then the alternative that will be chosen is to rent an equipment, due the purchase cost is bigger than the rental fee. In this case only considering the investment side. Keywords: Production, Investment, Excavator, Dump Truck, PWC, FWC